Top-down processing of submicron 45S5 Bioglass (R) for enhanced in vitro bioactivity and biocompatibility - Romeis, Stefan; Hoppe, Alexander; Detsch, Rainer; Boccaccini, Aldo R.; Schmidt, Jochen; Peukert, Wolfgang (2015)
45S5 Bioglass (R) (45S5BG - 45 wt.% SiO2, 24.5 wt.% CaO, 24.5 wt.% Na2O and 6 wt.% P2O5 glass forming system) is a frequently applied type A bioactive material, forming an inherent bond to bone and soft tissue. Recent studies for nanometer sized bioactive glasses (nBG) have indicated their great potential for several biomedical applications. It is recognized that cost-efficient processing routes are required for the development of submicron bioactive glasses, given the advantages associated with the nanoscale. In this study, the potential of top-down processing of 45S5BG by wet comminution in a stirred media mill is investigated and the key importance of the used solvents is revealed: whereas bioactive submicron particles can be produced in organic solvents, as shown exemplarily for n-pentanol, bioactivity is lost after processing in water. Analysis of the elemental constituents in the solid phase by ICP-OES indicates enhanced dissolution during processing in water, i.e. the glass composition is changing during processing. In n-pentanol the overall composition and structure is maintained and only the formation of surface carbonates is observed; flake-like particles are obtained. As a marker for bioactivity in vitro hydroxycarbonate apatite formation as determined by FTIR is used; biocompatibility is addressed by in vitro incubation with osteoblast like MG-63 cells. All-together, we propose wet comminution under controlled conditions as an appropriate technique to produce submicrometer bioactive glass particles with enhanced bioactivity. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: submicron 45S5 Bioglass (R); top-down; solvent influence; in vitro bioactivity and biocompatibility